Curriculum Design for Enhancing Students’ Entrepreneurial Skills: A Multi-Site Case Study at MTs PK Sunan Ampel and SMP Islam Al Fattah - Sony Eko Adisaputro; Akhyak Akhyak; Imam Fuadi (International Forum of Researchers and Lecturers, 2025)
Education is a conscious and structured effort aimed at creating an environment and process that actively facilitates learners in developing their full potential. This includes nurturing their spiritual and moral values, self-control, intelligence, strong character, and essential life skills required for personal development and meaningful contributions to society, the nation, and the global community. At its core, education serves to empower students to realize and utilize their capabilities for future life challenges. It acts as a foundational medium through which younger generations acquire essential life skills, enabling them to integrate effectively into society. Moreover, education plays a pivotal role not only in the personal growth of individuals but also in the advancement of a nation. High-quality education is defined by its capacity to equip students with the competence to confront and resolve real-world problems. This notion becomes increasingly critical as learners transition from academic settings to the workforce and community life, where they are expected to apply their knowledge and skills practically. However, the success or failure of educational outcomes is largely determined by the curriculum. A well-designed curriculum should cultivate critical awareness and empower students to navigate complex social and professional environments. It should also promote creativity, critical thinking, and collaboration, which are essential skills in today’s rapidly changing world. Furthermore, education should not be viewed merely as a means to acquire knowledge but as a holistic process that fosters emotional intelligence and social responsibility. By integrating various disciplines and encouraging interdisciplinary learning, education can help students develop a broader perspective on global issues, such as climate change, social justice, and economic inequality. In addition, the role of educators is crucial in this process.